2021
DOI: 10.1080/21655979.2021.1888578
|View full text |Cite
|
Sign up to set email alerts
|

Study on the occurrence law and green control of grape gray mold from the perspective of ecological balance

Abstract: With the increase of grape planting years, the base number of pathogenic seedlings and insect population is gradually rising. In addition, the introduction, breeding system and control of seedlings are not standardized and other human factors, the occurrence of Botrytis cinerea(B.cinerea) on grape is becoming more and more serious, resulting in a prominent problem of yield decline. In this paper, the occurrence of B.cinerea was monitored and its control effect was tested from the perspective of ecological bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Zhu et al [ 31 ] noticed a rapidly increasing trend of Penicillium, Nitrolancea, and Pseudomonas , while decreasing tendency of Fusarium and Mortierella, Nitrospira and Aquicella after applying dazomet. Shen et al [ 32 ] identified the dominant genus, Bacteroides, Flavobacterium, and Cytophaga, and the effect of carbendazim on bacterial community in arable land was mainly contributed by g- Proteobacterium . Fang et al [ 33 ] reported that carbendazim alters bacterial community mostly owing to γ- Proteobacteria , and carbendazim may suppress Pseudomonas, Mycobacterium, Bacillus, Arthrobacter, Burkholderia , and Streptococcus .…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al [ 31 ] noticed a rapidly increasing trend of Penicillium, Nitrolancea, and Pseudomonas , while decreasing tendency of Fusarium and Mortierella, Nitrospira and Aquicella after applying dazomet. Shen et al [ 32 ] identified the dominant genus, Bacteroides, Flavobacterium, and Cytophaga, and the effect of carbendazim on bacterial community in arable land was mainly contributed by g- Proteobacterium . Fang et al [ 33 ] reported that carbendazim alters bacterial community mostly owing to γ- Proteobacteria , and carbendazim may suppress Pseudomonas, Mycobacterium, Bacillus, Arthrobacter, Burkholderia , and Streptococcus .…”
Section: Resultsmentioning
confidence: 99%
“…Grape is an important fruit crop worldwide with huge economic value. With the increase in grape planting years, the base number of pathogenic seedlings and insect population is gradually increasing [1]. The occurrence of Botrytis cinerea on grape, the ubiquitous necrotrophic fungal pathogen, is becoming more and more serious, resulting in a prominent problem of yield and quality decline [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Gray mold disease, caused by Botrytis cinerea , is one of the most serious fungal diseases affecting flowers, fruits, leaves, and stems; it is difficult to control because the pathogen can survive in soil and plant residue for a long time ( 3 , 4 ). B. cinerea is one of the most devastating postharvest diseases that cause gray mold during transportation and storage of tomato ( Solanum lycopersicum ), grapevine ( Vitis vinifera L.), and over 200 other plant species and is responsible for significant direct losses that total 20% to 30% and even reach 50% in severe cases (Chinese research data) ( 5 , 6 ). It is necessary to efficiently control the occurrence and spread of gray mold disease.…”
Section: Introductionmentioning
confidence: 99%